Quantification of Xylanolytic and Cellulolytic Activities of Fungal Strains Isolated from Palmaria palmata to Enhance R-Phycoerythrin Extraction of Palmaria palmata: From Seaweed to Seaweed - Yoran Le Strat; Margaux Mandin; Nicolas Ruiz; Thibaut Robiou du Pont; Emilie Ragueneau; Alexandre Barnett; Paul Déléris; Justine Dumay (Marine Drugs, 2023)
R-phycoerythrin (R-PE) can be enzymatically extracted from red seaweeds such as Palmaria palmata. This pigment has numerous applications and is notably known as an antioxidant, antitumoral or anti-inflammatory agent. Enzymes secreted by P. palmata associated fungal strains were assumed to be efficient and adapted for R-PE extraction from this macroalga. The aim of the present study was to quantify both xylanolytic and cellulolytic activities of enzymatic extracts obtained from six Palmaria palmata derived fungal strains. Degradation of P. palmata biomass by fungal enzymatic extracts was also investigated, focused on soluble protein and R-PE extraction. Enzymatic extracts were obtained by solid state fermentation. Macroalgal degradation abilities were evaluated by measuring reducing sugar release using DNS assays. Soluble proteins and R-PE recovery yields were evaluated through bicinchoninic acid and spectrophotometric assays, respectively. Various enzymatic activities were obtained according to fungal isolates up to 978 U/mL for xylanase and 50 U/mL for cellulase. Enzymatic extract allowed high degrading abilities, with four of the six fungal strains assessed exhibiting at least equal results as the commercial enzymes for the reducing sugar release. Similarly, all six strains allowed the same soluble protein extraction yield and four of them led to an improvement of R-PE extraction. R-PE extraction from P. palamata using marine fungal enzymes appeared particularly promising. To the best of our knowledge, this study is the first on the use of enzymes of P. palmata associated fungi in the degradation of its own biomass for biomolecules recovery.